SMUT MANHWA AS A SAFE SPACE: WOMEN'S AGENCY IN CONSTRUCTING IMAGES OF DESIRE AND GENDER RELATIONS - Citra Farahma Devi; Ahmad Ridwan; Refti Handini Listyani; M. Jacky; Muhammad Faruki B (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study examines how women in Indonesia construct smut manhwa as a safe space, and how this practice illustrates their agency in shaping sexual desire and gender relations within patriarchal structures. Using a phenomenological approach with four informants and three rounds of thematic coding, this study analyses data from online interviews. The findings reveal that women's agency operates ambivalently, simultaneously establishing hidden normative boundaries and negotiating alternatives to patriarchal norms. Women utilize digital resources to access restricted desires, continuously sorting and interpreting content reflectively. A comparison with China highlights how different forms of structural control (social stigma vs. state censorship) shape distinct forms of women's agency. This research contributes to the understanding of women not as passive consumers, but as reflective actors who continuously negotiate the meanings of desire, gender relations, and bodily autonomy within structural constraints.